Multiscale Hybrid Modeling of Proteins in Solvent: SARS-CoV2 Spike Protein as Test Case for Lattice Boltzmann — All Atom Molecular Dynamics Coupling (Communications in Computational Physics, 2023)
Physiological solvent flows surround biological structures triggering thereincollective motions. Notable examples are virus/host-cell interactions and solvent-mediated allosteric regulation. The present work describes a multiscale approach joining the Lattice Boltzmann fluid dynamics (for solvent flows) with the all-atom atomistic molecular dynamics (for proteins) to model functional interactions between flowsand molecules. We present, as an applicative scenario, the study of the SARS-CoV-2virus spike glycoprotein protein interacting with the surrounding solvent, modeled asa mesoscopic fluid. The equilibrium properties of the wild-type spike and of the Alphavariant in implicit solvent are described by suitable observables. The mesoscopic solvent description is critically compared to the all-atom solvent model, to quantify theadvantages and limitations of the mesoscopic fluid description.
Keywords: SARS-CoV-2; biophysics; lattice Boltzmann; molecular dynamics.